Práticas intraempreendedoras em empresas graduadas em incubadoras - Straub, Anderson Luiz (2014)
Working dissertation that has the objective to describe the influence that the incubation process was assimilated and transmitted by senior companies in incubators, the adoption of intrapreneurial practices. It also seeks to understand what intrapreneurial practices were disseminated during the incubation of companies, from the point of view of the management of the incubator, and which practices and with what intensity were adopted in enterprises, from the point of view of entrepreneurs. The research is qualitative characteristic and was conducted through semistructured interviews with two distinct audiences: the first was the incubator and the second active companies graded by the incubator. In the script of qualitative interview enterprises, two quantitative assessments, to understand the perception that entrepreneurs had the incubator and the spread of 20 intrapreneurial practices and other related to the evaluation of the intensity of adoption of these intrapreneurial practices were applied. The work was developed through field research, initially with an interview with the management of the incubator and subsequently with eight entrepreneurs who had their businesses and their projects hatched between 1995 and 2009. The survey results showed that the graduated companies in the incubator partially adopt and low intensity intrapreneurial practices in their daily lives, and this adoption did not have significant influence or no influence. The results also showed that, indeed, the incubator does not spread in a planned intrapreneurial practices during the incubation of companies, however, it was found that some practices were widespread, but, involuntarily.